51=3-6y

Simple and best practice solution for 51=3-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 51=3-6y equation:



51=3-6y
We move all terms to the left:
51-(3-6y)=0
We add all the numbers together, and all the variables
-(-6y+3)+51=0
We get rid of parentheses
6y-3+51=0
We add all the numbers together, and all the variables
6y+48=0
We move all terms containing y to the left, all other terms to the right
6y=-48
y=-48/6
y=-8

See similar equations:

| 2(3n-1)=2(2n+5 | | 3x-7x-7=-4x+6-7 | | 6+8v=5v | | d+d/18+4=22 | | 8x–2–7x=-9 | | 13x-12=183 | | 5x-14=2x+3x+16 | | 3. 6x+18=30 | | 8(8k+1)=8+2k | | –3+–3p=12 | | 7b+14=53 | | 2(x+1)+3(x-5)=7 | | -1(5x+4)=3x-52 | | 48+w=30 | | 10x+3+3x=5x+1+8x*2 | | 12=-0.15f | | 4=x-3/8=12 | | 15c=-9-8c | | -14=7w+200w+8.5 | | 3x-3+5=6x+1 | | 6x+6=3x-213x−21 | | -12x=-42 | | 6y+3+2y+8=43 | | 9x+18=144 | | 5d-2=5 | | 2x²+4x-2=0 | | 67=11^x | | 5j+9-10j=-2j+3 | | 10−3 | | 2(2−7y)−5=111 | | -5(x-2)=2(1-2x)-8 | | 12-8x=3-5x |

Equations solver categories